ERP-Based Management Information System for MSMEs in Indonesia: A Systematic Literature Review - Hasanah, Nur; Saputra, Dhanar Intan Surya; Hiiyatin, Dewi LaeIa (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2024)
This study is a systematic literature review on ERP-Based Management Information Systems for MSMEs (Micro, Small and Medium Enterprises) in Indonesia. Through an analysis of previous studies, the findings show that the use of ERP can integrate various business functions in one integrated system, automate business processes, and provide fast access to real-time information, thereby increasing the operational efficiency and productivity of MSMEs. The research method in this paper is carried out systematically, starting with identifying research questions and determining the paper's contribution. Furthermore, a search strategy was carried out, selecting relevant and quality documents and extracting data to produce output in this study. The results show that ERP provides integrated data access, enables better and more informed decision-making, and helps plan business growth better. Although ERP adoption requires initial investment and wise management, the use of ERP has proven to impact the competitiveness and growth of MSMEs in Indonesia positively. This study will provide an in-depth understanding of the ERP-Based Management Information System and contribute to developing strategies and policies that support the growth and sustainability of the MSME sector in Indonesia.